PENDIDIKAN KARAKTER DALAM PEMBELAJARAN AGAMA KATOLIK DI SMA SANTO BONAVENTURA MADIUN - Martina Murlani (Bahasa Indonesia, 2019)
Character and national culture became a sharp concern of society. This paper discusses one of the practical alternative solution. It is so basic, that is, character education during the Catholic religion teaching learning process. This requires a change of attitude and new skill of its teacher (condito sine qua non) So as to accomplish the character of nationalism. A character of good nationality is the actualization of the quality of Indonesian. As formulated in the funcition and purpose of national education. The research shaus that the character education in SMA Saint Bonaventura Madiun is implemeted trough the routine activities, spontaneous activities and the modelling that includes the development of culture norms and national character such as religious values, discipline, care to environment, social care, honesty and nationalism. The phases are: implementing, monitoring, evaluating and follow up action.